Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1037/a0037992
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving antecedents of secure base script knowledge: A comparative analysis of young adult attachment representations.

Abstract: Based on a sub-sample (N = 673) of the NICHD Study of Early Child Care and Youth Development (SECCYD) cohort, this paper reports data from a follow-up assessment at age 18 years on the antecedents of secure base script knowledge, as reflected in the ability to generate narratives in which attachment-related difficulties are recognized, competent help is provided, and the problem is resolved. Secure base script knowledge was (a) modestly to moderately correlated with more well established assessments of adult a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
121
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(155 citation statements)
references
References 58 publications
17
121
2
3
Order By: Relevance
“…Nevertheless, large-scale longitudinal studies and several meta-analyses have indicated that the magnitude of associations between childhood experiences with attachment figures and adolescent/adult representations of attachment is weaker than was widely assumed (e.g., Atkinson et al, 2000; Groh et al, 2014; Steele et al, 2014; de Wolff & van IJzendoorn, 1997), even when findings can be interpreted as being consistent with a causal effect of maternal sensitivity on attachment security (Bakermans-Kranenberg, Juffer, & van IJzendoorn, 2003). Effects of even weaker magnitudes have been reported when measures of attachment security obtained during infancy/toddlerhood are used as predictors of mental representations of attachment during adolescence and adulthood in large-scale longitudinal studies (e.g., Sroufe et al, 2005; Steele et al, 2014). …”
mentioning
confidence: 93%
“…Nevertheless, large-scale longitudinal studies and several meta-analyses have indicated that the magnitude of associations between childhood experiences with attachment figures and adolescent/adult representations of attachment is weaker than was widely assumed (e.g., Atkinson et al, 2000; Groh et al, 2014; Steele et al, 2014; de Wolff & van IJzendoorn, 1997), even when findings can be interpreted as being consistent with a causal effect of maternal sensitivity on attachment security (Bakermans-Kranenberg, Juffer, & van IJzendoorn, 2003). Effects of even weaker magnitudes have been reported when measures of attachment security obtained during infancy/toddlerhood are used as predictors of mental representations of attachment during adolescence and adulthood in large-scale longitudinal studies (e.g., Sroufe et al, 2005; Steele et al, 2014). …”
mentioning
confidence: 93%
“…Al respecto, hay evidencias de que la sensibilidad, tanto materna como paterna, son precedentes importantes para un guion de base segura en la adultez (Hesse & Main, 2000;Steele et al, 2014;Waters et al, 2013;Waters & Rodrigues-Doolabh, 1998;Waters & Cummings, 2000). Estudios previos han demostrado niveles bajos de sensibilidad materna en diversos grupos socioeconómicos del contexto peruano (Nóblega, 2012; Nóblega, Bárrig, Núñez del Prado & Conde, investigación en curso).…”
Section: Discussionunclassified
“…En el campo del apego adulto hay diferentes perspectivas para acceder al estudio de estas representaciones (Steele et al, 2014). Por un lado, es posible analizar la narrativa de la persona como en la Entrevista del Apego Adulto (AAI, por sus siglas en inglés) o determinar los niveles de ansiedad y evitación de un individuo como dimensiones de su estilo de apego (Mikulincer & Shaver, 2007) o evaluar la inclusión del fenó-meno de base segura en sus guiones (Waters & Rodrigues-Doolabh, 1998;Waters et al, 2015).…”
unclassified
See 1 more Smart Citation
“…Waters & Rodrigues-Doolabh, 2001; Dykas, Woodhouse, Cassidy, & Waters, 2006). Narratives that conform more closely to the secure base script are associated with attachment security, as measured both in the AAI and with self-reported attachment styles (Dykas et al, 2006; Mikulincer, Shaver, Sapir-Lavid, & Avihou-Kanza, 2009), and with the quality of the early caregiver-child relationship (Steele et al, 2014) as well as with continued parental support throughout childhood and adolescence (Vaughn et al, 2016). …”
Section: Introductionmentioning
confidence: 99%